Analisis Penentuan Harga Pokok Produksi Pada UD. Madina Kecamatan Tondon Kabupaten Toraja Utara - Anastasya Sampe Lantang; Astriwati Biringkanae; Lisa Kurniasari Wibisono (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
Anastasya Sampe Lantang, 2023. Analysis of determining the cist of production at UD. Madina, Tondon District, North Toraja Regency. The cost of production is very influential in calculating the profit and loss of a business, if a business is not careful and not precise in determining the cost of production and in classifying the elements of costs used it can result in losses. Production costs must be properly recorded and calculated correctly so as to produce the right and correct cost of production. The problem of this research is how much is the cost of production at UD. Madina, Tondon District, North Toraja Regency and the objectives to be achieved in this study are to determine the cost of production at UD. Madina. The type of research used in this research is descriptive quantitative research which aims to describe production costs and production costs. Data collection techniques are carried out by collecting data related to research in the field and calculating it using the full costing method. The results of this study concluded that by using the full costing method, for 1 unit of door frame it was Rp. 271,652, for 1 unit of window frame it was Rp. 352,874 and for 1 unit of door it was Rp. 492,974. The profit desired by UD. Madina is 25%, so the selling price for each unit is IDR 490,874 for 1 door frame unit, IDR 339,565 for 1 window frame unit, and IDR 618,717 for 1 door unit.